Traditional tonifying polyherbal infusion, Jatu-Phala-Tiga, exerts antioxidant activities and extends lifespan of Caenorhabditis elegans - Wetchakul, Palika (BMC Complement Altern Med, 2019)
BACKGROUND: The imbalance between the generation of free radicals and natural cellular antioxidant defenses, known as oxidative stress, can cause oxidation of biomolecules and further contribute to aging-associated diseases. The purpose of this study was to evaluate the antioxidant capacities of Thai traditional tonifying preparation, Jatu-Phala-Tiga (JPT) and its herbal ingredients consisting of Phyllanthus emblica, Terminalia arjuna, Terminalia chebula, and Terminalia bellirica and further assess its effect on longevity. METHOD: Antioxidant activities of various extracts obtained from JPT and its herbal components were carried out using well-established methods including metal chelating, free radical scavenging, and ferric reducing antioxidant power assays. Qualitative analysis of the chemical composition from JPT water extract was done by high-performance liquid chromatography tandem with electrospray ionisation mass spectrometry. The effect of JPT water extract on the lifespan of Caenorhabditis elegans were additionally described. RESULTS: Among the extracts, JPT water extract exerted remarkable antioxidant activities as compared to the extracts from other solvents and individual constituting plant extract. JPT water extract was found to possess the highest metal chelating activity, with an IC(50) value of 1.75 ± 0.05 mg/mL. Moreover, it exhibited remarkable scavenging activities towards DPPH, ABTS, and superoxide anion radicals, with IC(50) values of 0.31 ± 0.02, 0.308 ± 0.004, and 0.055 ± 0.002 mg/mL, respectively. The ORAC and FRAP values of JPT water extract were 40.338 ± 2.273 μM of Trolox/μg of extract and 23.07 ± 1.84 mM FeSO(4)/mg sample, respectively. Several well-known antioxidant-related compounds including amaronols, quinic acid, gallic acid, fertaric acid, kurigalin, amlaic acid, isoterchebin, chebulagic acid, ginkgolide C, chebulinic acid, ellagic acid, and rutin were found in this extract. Treatment with JPT water extract at 1 and 5 mg/mL increased C. elegans lifespan under normal growth condition (7.26 ± 0.65 vs. 10.4 0± 0.75 (p < 0.01) and 10.00 ± 0.73 (p < 0.01) days, respectively). CONCLUSIONS: The results indicated that JPT and its herbal ingredients exhibited strong antioxidant activities, in particular the water extract of the polyherbal tonic. These findings rationalize further investigation in JPT infusion as a promising agent for anti-aging and oxidative stress prevention.